A STUDY OF THE BANANA FARMING INDUSTRY CHIPS IN KUALA LANGKAT - M. Sidik Tarigan; Desi Sri Pasca Sari Sembiring (Yayasan Sinergi Multidimensi Kreatif, 2024)
Bananas are non-branched plants and are classified as monocots. The trunk that forms the tree is a pseudo-stem, consisting of leaf fronds that are arranged in an orderly manner, the branching of the plant is sympodial type (the trunk of the tree is difficult to determine) with an elongated end meristem and forms flowers and fruits. The fruit at the bottom of the banana stem is bulging in the form of a tuber called a hump. The potential of the banana chips business itself is also very good, so it's not surprising that now many are taking advantage of banana chips business opportunities. By taking advantage of business activities by offering banana chips, it is actually able to bring in a fairly high turnover. The public's demand for processed banana chips from time to time continues to increase, making the potential of this business very promising. The banana chips business is indeed very easy to run with a capital that is not too large. The banana chips business also has a lot of enthusiasts so it's not surprising that banana chips are selling well in the market. The problem is how the Financial Feasibility of the Banana Chips Business can increase family welfare income. The method of reviewing the case study is to analyze in depth the financial feasibility of the banana chips business in a specific location, namely Jln. Setia Budi Pasar 1, Medan Selayang District, Medan City. The location of Peanaman Pisang is in Kuala Langkat. This research is descriptive, that is, it describes what it is. Then a revenue analysis table is made where the goal is to analyze the income from the sale of banana chips. Results of the Analysis of the Farmer Business Study The business of selling banana chips in one week can get a total income of Rp. 8,610,000 with a net profit of Rp. 6,297,000 after deducting all production costs. Banana Chips Business can increase family income and is not too complicated to run.